1995
DOI: 10.1002/jcp.1041630324
|View full text |Cite
|
Sign up to set email alerts
|

Activation of junB and c‐myc primary response genes by interleukin 9 in a human factor‐dependent cell line

Abstract: Interleukin 9 (IL-9) stimulates the proliferation of various hematopoietic cell types. To elucidate the molecular mechanisms underlying the cell proliferation action, immediate-early gene expression elicited by IL-9 in a human factor-dependent cell line, MO7e, was studied. IL-9 stimulation resulted in a rapid and transient elevation of primary response genes including junB and c-myc. The differential effects of protein kinase inhibitors, herbimycin A, genistein, and H-7 on the steady-state mRNA level and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…There is a growing amount of evidence that JunB may play a role distinct from that of c-Jun in the regulation of cell growth. junB expression is distinct from c-jun expression in many tissues (57) and during differentiation (25) and is stimulated independently of c-jun expression in response to a number of growth factors (1,37). c-Jun can homodimerize and heterodimerize with other AP1 factors, whereas JunB can only heterodimerize (20); furthermore, c-Jun strongly transforms rat embryo fibroblasts and transactivates via the TRE from a variety of promoters (58), whereas JunB is weakly transforming and its transactivation potential is more promoter specific (32).…”
Section: H Following Epo Stimulation Of Hcd57 Cells and Suppression mentioning
confidence: 99%
“…There is a growing amount of evidence that JunB may play a role distinct from that of c-Jun in the regulation of cell growth. junB expression is distinct from c-jun expression in many tissues (57) and during differentiation (25) and is stimulated independently of c-jun expression in response to a number of growth factors (1,37). c-Jun can homodimerize and heterodimerize with other AP1 factors, whereas JunB can only heterodimerize (20); furthermore, c-Jun strongly transforms rat embryo fibroblasts and transactivates via the TRE from a variety of promoters (58), whereas JunB is weakly transforming and its transactivation potential is more promoter specific (32).…”
Section: H Following Epo Stimulation Of Hcd57 Cells and Suppression mentioning
confidence: 99%
“…hIL-9 has been demonstrated to induce c-Myc and JunB expression in a human megakaryocytic leukemia cell line (19). To understand the functional importance of the intracellular domains of hIL-9R␣ in the expression of primary response genes and to correlate expression of these genes with cell growth, we examined expression of c-myc, junB, c-jun, and c-fos in response to hIL-9 by Northern blot analysis.…”
Section: Il-9 Receptor ␣ Domains Critical For Signal Transductiondiffmentioning
confidence: 99%
“…Several homologous sequences, such as the BOX1 consensus sequence and a serine-rich region, which were demonstrated to be important for IL-2R␤ function (16), are also present in the cytoplasmic region of human IL-9R␣ (hIL-9R␣). Recently, it has been shown that several biochemical events including tyrosine phosphorylation of JAK kinases, activation of signal transducers and activators of transcription (STAT) proteins, and expression of nuclear protooncogenes are involved in IL-9-mediated signal transduction (17)(18)(19). In the present study, a series of deletions and point mutations were made in the cytoplasmic region of hIL-9R␣.…”
mentioning
confidence: 99%
“…Our recent studies (9)(10)(11)(12) have shown that the induction of c-myc and junB, two primary response genes, is a signaling event downstream of JAK͞STAT (Janus kinase͞signal transducer and activator of transcription; refs. 13 and 14) activation in IL-9-mediated signal transduction.…”
mentioning
confidence: 99%